APPLICATION OF BUSINESS ETHICS THE RASULULLAH'S WAY IN BUSINESS DEVELOPMENT AT KOPPONTREN AUSATH PP. DARUSSALAM BLOKAGUNG - Inayah, Nurul; Ustanti, Mira; Khusnudin, Imam; Sholihah, Imroatun (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
The purpose of this study was to determine the application of Islamic business ethics in developing business at the AUSATH PP Koppontren PP Darussalam Blokagung. The data analysis tool used in this research is descriptive qualitative. Based on the results of the research and discussion that has been carried out, it can be concluded that the application was carried out to develop business at the AUSATH PP Koppontren. Darussalam has been clearly illustrated in accordance with the business principles exemplified by the Prophet, namely: 1) Siddiq ; Honest, meaning that the delivery of information about everything that is done from Ausathmart to consumers is conveyed purely without adding lies. 2) Trust; can be trusted to deliver information related to promotions and the condition of the goods correctly and not by coercion. 3) Fatannah ; smart, meaning that the delivery of information carried out by Ausathmart to consumers must show the intelligence of the Ausathmart unit manager in developing his business. 4) Tablighi ; delivery of information, promotion and delivery of goods is carried out properly and correctly in accordance with what was conveyed at the beginning and does not harm any party. The implication of the research conducted for managers is to complement the needs of consumers, especially students to make it easier for students not to leave Islamic boarding schools frequently, for other researchers, they can conduct research related to student satisfaction which has never been done before.